SPSS Base 7.5 for Windows : user`s guide (SPSS, 1997)
This user\'s guide documents all features of the software for SPSS Bases 7.5, including: data definition and other features of the Data Editor, data modification and file management; output management including the SPSS Navigator: statistics and graphics procedures including pivot tables; chart editing; production mode operation; and utilities for getting information (including help) and controlling the environment. The guide also covers the additional higher-level statistical procedures now part of SPSS Base. These procedures include: factor, discriminate, cluster, quick cluster and proximities. Statistical procedures are accompanied by examples of output. Further information and help concerning procedures and the output they produce is provided by the \"SPSS Base 7.5 Applications Guide\".
Keywords: SPSS; lékařská informatika